Factors Affecting the User Satisfaction of Online Catalog Information Systems (UNSLA) - Masriyatun, Masriyatun; Fatmawati, Rustania (Universitas Pendidikan Indonesia, 2024)
UPT Online Catalog Application Library is one of Library Application used by the user at University of Sebelas Maret Surakarta. Statistical results from the assessment and review of the user in 2022, show that the satisfaction level is still low and there are various complaints from the users against the UPT Online Catalog Application of the Library of the University of Sebelas Maret Surakarta. Thus, researchers are interested in discussing this using quantitative research methods. Quantitative research with this type of associative research is used to look at relationships or influences between two or more variables. Researchers used Slovin's formula to determine the sample. The population in the research are 671. Then, the results of 87 respondents were obtained as a sample. The result of this research shows that all variables including content, accuracy, timeliness, form, ease of use have a relationship with user satisfaction of the UPT Library online catalog information system of University of Sebelas Maret Surakarta. The influence of free variables using the UPT library online catalog information system on user satisfaction is 38.8% while the rest (100% - 38.8%) is 61.2 percent influenced by other variables. Suggestions to libraries to improve the UPT Online Catalog Information System of the Library of the University of Sebelas Maret Surakarta include content, accuracy, timeliness, form, and ease of use in order to provide satisfaction and positive assessment of the users.